1990
DOI: 10.1007/bf00040364
|View full text |Cite
|
Sign up to set email alerts
|

Yield and adaptation of hexaploid spring triticale

Abstract: Gains in yield and stability were analysed using grain yield data from the 8th to the 14th International Triticale Yield Nursery (ITYN) and differences in adaptation between complete and substituted triticales (X Triticosecale Wittmack) were examined. A trend of improving yield and adaptation was observed. As highly significant genotype x site interaction each year was not adequately described using regression analysis, yield stability was examined by ranking genotypes within sites and summarizing scores for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
188
0
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(194 citation statements)
references
References 9 publications
0
188
0
6
Order By: Relevance
“…We also used the methodology described by Fox et al (1990), who proposed a nonparametric superiority measure for general adaptability using stratified ranking of cultivars. Ranking was done at each location separately and the number of sites at which the cultivar occurred in the TOP, MID, and LOW third of the ranks was computed.…”
Section: S Imentioning
confidence: 99%
See 3 more Smart Citations
“…We also used the methodology described by Fox et al (1990), who proposed a nonparametric superiority measure for general adaptability using stratified ranking of cultivars. Ranking was done at each location separately and the number of sites at which the cultivar occurred in the TOP, MID, and LOW third of the ranks was computed.…”
Section: S Imentioning
confidence: 99%
“…According to Fox et al (1990) a genotype usually found in the top third of entries across environments can be considered relatively well adapted and stable. Thus, in our study, the most stable genotype was Karahan-99 because it ranked in the top third of genotypes in a high percentage of environments (i.e., had a high TOP value), followed by the AL-2 and AL-3 genotypes, with the least-desirable genotypes being AL-4, Yakar-99, AL-5 and AL-1 (Table 3).…”
Section: Test Statistics For (Smentioning
confidence: 99%
See 2 more Smart Citations
“…Ele obteve essa estimativa pela seguinte equação: Portanto, as cultivares que apresentassem as menores variâncias nos postos foram consideradas as mais está-veis. Fox et al (1990) propuseram uma estratificação destes postos para a definição de estabilidade de determinada cultivar. Eles sugeriram, de maneira mais intuitiva, que as cultivares cujas produções ocupassem consistentemente o terço superior dos postos (menores valores = maiores produções) seriam estáveis e teriam características favoráveis à seleção, ao passo que aquelas que ocupassem o terço inferior dos postos (maiores valores = menores produções) seriam igualmente estáveis, mas não seriam selecionáveis, devido à baixa produção.…”
Section: Medidas Não-paramétricas De Estabilidadeunclassified